2007
DOI: 10.1016/s1006-7191(07)60033-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment on damping behaviour of the magnesium wrought alloy AZ61

Abstract: The effect of isochronal heat treatments for 1 h on variation of damping, hardness and microstructural change of the magnesium wrought alloy AZ61 was investigated.Damping and hardness behaviour could be attributed to the evolution of precipitation process. The influence of precipitation on damping behaviour was explained in the framework of the dislocation string model of Granato and Lücke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…And it was interpreted successfully by the IF model postulated by Peguin and his coworkers for aluminum [5]. Similar results have been obtained in other studies [19,20]. IF related to microplasticity is characterized by the Eq.…”
Section: The Relationship Between Internal Friction (If) and Microplasupporting
confidence: 82%
“…And it was interpreted successfully by the IF model postulated by Peguin and his coworkers for aluminum [5]. Similar results have been obtained in other studies [19,20]. IF related to microplasticity is characterized by the Eq.…”
Section: The Relationship Between Internal Friction (If) and Microplasupporting
confidence: 82%
“…There is good agreement between the theory and experimental results at relatively low value of strain amplitudes, while a deviation from the straight line occurs beyond the strain amplitude of about 0.5%, denoted as e cr2 . In fact, another type of IF has been observed and which is thought to be associated with plastic strain [15][16][17]. The plastic IF explained by Peguin [17] can be obtained by the subtraction of Q 0 À 1 and Q h À 1 (Fig.…”
Section: Internal Friction (If)mentioning
confidence: 99%
“…In general, the corrosion rate of Mg alloys is affected by the precipitated phases significantly. Heat treatment is one of the effective methods to adjust the second phases and therefore to affect the mechanical properties, as well as corrosion properties of Mg alloys [13][14][15]. According to our previous work, it was confirmed that the mechanical properties were closely linked to the different precipitated phases in Mg 95.8 Gd 3 Zn 1 Zr 0.2 alloy with LPSO structure before and after heat treatment [3].…”
Section: Introductionmentioning
confidence: 84%